(untitled) (Wudil Journal of Science and Technology Education, 2025)
The present study was undertaken to estimate the genetic variability, heritability and genetic advancement for growth and yield parameters among some local and improved sweet potato(Ipomoea batatas(L.) Lam.] varieties obtained from four different locations in Nigeria. The experiment was laid in a randomized complete block design with three replications between the end of May – the end of September 2024 at the Federal University of Technology Owerri Research Farm. Analysis of variance revealed highly significant differences (p<0.05) among the genotypes for both thegrowth and yield parameters. The phenotypic coefficient of variation was higher than genotypic coefficient of variation for all the traits. High (>20 %) genotypic coefficient ofvariation (GCV) and phenotypic coefficient variation (PCV) were observed for number of marketable root per hectare, weight of top biomass per hectare, number of unmarketable root per hectare, sprout countand number of leaves. It indicated the existence of broad genetic gain, which would be amenable for further selection. High heritability (>60 %) were recorded for the following characters: weight of top biomass, sprout count, petiole length, root diameter, leaf width, number of leaves, plant girth, vine length, leaf length, number of unmarketable root, root length and number of marketable root (60%). Highgenetic advance as percentageover mean GAM% (>20 %) were recorded for the characters namely: Weight of top biomass, number of unmarketable root, sprout count, number of marketable root, number of leaves and root diameter. Traits with high heritability and GAM% value are governed by additive genes and selection would be efficient forfurther crop improvement.It is therefore recommended, that more accessions can be utilized in assembling varieties especially for characters which have a broad GCV value.